Does Chinese Vegetable Oil Consumption Have Positive Implications for the Indonesia-China Trade Balance? - Jan Horas Veryady Purba (Integrated Journal of Business and Economics (IJBE), 2020)
Indonesia is the world's CPO producer country, and at the same time, Indonesia also the largest exporter of CPO in global market. Some of the main countries that are becoming export destinations for Indonesia CPO are India, China, the European Union, USA and Pakistan. Empirically, it is seen that the phenomenon of widening gap in Chinese vegetable oil consumption patterns, where consumption growth is higher than domestic production growth. This boosted Indonesia's CPO exports to China and subsequently had an impact on the Indonesia-China trade balance. Analytical method used is ordinary least square (OLS), which is arranged in two-equation models. Findings of this study conclude that (a) Indonesia's CPO exports to China are affected by the increase in consumption of vegetable oils in China. This is consistent with the expected hypothesis; (b) the value of Indonesia's CPO exports to China has a positive impact and helps reduce Indonesia's trade balance deficit. This is consistent with the research hypothesis. Indonesia's CPO exports have a positive impact on the Indonesia-China trade balance, in particular contributing to overcome the Indonesia-China trade balance deficit. This research shows that CPO is Indonesia's strategic commodity that helps overcome Indonesia's trade balance deficit.